Relative efficacy of anti-Plasmodium vivax malaria combination drugs in preventing transmission to two major Anopheles mosquitoes in the first few days of treatment - Martinez, Erika Gómez; Alencar, Rodrigo Maciel; Santana, Rosa Amélia Gonçalves; Barbosa, Laila Rowena Albuquerque; Almeida, Anne Cristine Gomes de; Mwangi, Victor Irungu; Rocha, Sarah Regiane do Nascimento; de Souza, Layne Even Borges; Silva, Lucyane Mendes; Pinilla, Yudi Tatiana; Becker, Norbert; Monteiro, Wuelton Marcelo; et al. (International journal of infectious diseases, 2025)
Objectives - The World Health Organization recommends three drug anti-malarial combinations: cloroquine+primaquine, artesiminin+primaquine, and cloroquine+tafenoquine. These combinations aim to eradicate Plasmodium by disrupting its life cycle within the human body. We evaluated the effect of these medications on the vectorial competence of two main vectors in the New World. - Methods - We recruited patients diagnosed with malaria vivax from a primary care in Manaus, Amazonas. To determine how different treatments affected vectors, we collected blood samples prior to treatment at the hospital and at six intervals over the next 68 hours at the patient's homes. These samples were used to infect Anopheles darlingi and Anopheles aquasalis. To assess the potential for Plasmodium transmission by bite to a new human host, we analyzed the infection intensity, infection rate, and presence of parasites in the salivary gland of the mosquitoes. - Results - The results show the infection of the mosquitoes fed with the patient's blood during the first days of treatment with all three drug combinations. However, the cloroquine+tafenoquine combination was the least effective while artesiminin+primaquine was the most effective. - Conclusions - In the first few days of treatment, two main vectors continue to spread malaria vivax from patients, potentially contributing to the ongoing transmission in malaria-endemic regions.
Online verfügbar: 12. November 2024, Artikelversion: 6. Dezember 2024
Gesehen am 14.03.2025